Comparative analysis of consensus algorithms for distributed ledger technologies - Bilichenko, D.; Vitiuk, K.; Oliynykov, R. (Radiotekhnika, 2024)
The comparative characteristic of consensus algorithms in distributed ledgers based on different technologies such as blockchain and directed acyclic graph is given in the article. Advantages and disadvantages of GHOST, Tangle and Hashgraph consensus algorithms are given, as well as recommendations of optimal variant selection.